Correlation between the Circadian Rhythm of Resistance to Extreme Temperatures and Changes in Fatty Acid Composition in Cotton Seedlings. - Rikin, A. (1993)
Fluctuations in fatty acid composition were examined in cotton (Gossypium hirsutum L. cv Deltapine 50) leaves during light-dark cycles of 12:12 h and under continuous light and were correlated to the rhythmic changes in chilling (5[deg]C) resistance (CR) and heat (53[deg]C) resistance (HR). The chilling-resistant and chilling-sensitive phases developed in the dark or the light period, respectively, and this rhythm persisted under continuous light for three cycles. The heat-resistant phase developed in the light period and an additional peak of HR occurred in the middle of the dark period. Under continuous light, only one peak of HR developed, lasting from the middle of the subjective night to the middle of the subjective day. The amounts of palmitic and oleic acids were constant during the light-dark cycle and under continuous light, but those of linoleic and linolenic acids fluctuated, attaining a high level in the middle of the dark period or the subjective night, and a low level in the middle of the light period or the subjective day. A low temperature of 20[deg]C induced CR and affected changes in fatty acid composition similar to those that occurred during the daily CR phase. A high temperature of 40[deg]C induced HR but did not affect changes in fatty acid composition. The results in their entirety show that the CR that develops rhythmically as well as the low-temperature-induced CR coincide with increased levels of polyunsaturated fatty acids. No correlation is found between changes in fatty acid composition and the HR that develops rhythmically or the high-temperature-induced HR.